2015
DOI: 10.13080/z-a.2015.102.032
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of phosphorus forms and fractions in Retisol under different soil liming management

Abstract: Investigations on phosphorus (P) distribution in a naturally acid and limed moraine loam, Bathypogleyic Dystric Glossic Retisol were conducted in a site of a long-term experiment at the Vėžaičiai Branch of Lithuanian Research Centre for Agriculture and Forestry in 2008 and 2011. The aim of the present study was to determine the distribution of different phosphorus forms and fractions in naturally acid soil limed for a long time (62 years). During this study different amounts (18.4 and 104.9 t ha -1 ) of lime m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…It increased from 14.2 to 53.1 mg kg (Table 3). Similar results were reported by Hartono et al [8] and Jokubauskaite et al [10]. It is likely related to an increase in adsorption and precipitation of P with the addition of excess Ca derived from lime.…”
Section: Hagereselam Soil With Different Rates Of Lime Applicationsupporting
confidence: 90%
See 3 more Smart Citations
“…It increased from 14.2 to 53.1 mg kg (Table 3). Similar results were reported by Hartono et al [8] and Jokubauskaite et al [10]. It is likely related to an increase in adsorption and precipitation of P with the addition of excess Ca derived from lime.…”
Section: Hagereselam Soil With Different Rates Of Lime Applicationsupporting
confidence: 90%
“…Analysis of the organic P fractional composition showed that the major portion of the total extractable organic P was extracted by NaOH solutions (Table 3). These phosphorus compounds are more readily mineralized because they are constituents of the newly incoming organic residues as well originating from cells of microorganisms [10]. Although not statistically significant, the organic P contained in both NaOH and HCl fractions decreased with addition of lime.…”
Section: Hagereselam Soil With Different Rates Of Lime Applicationmentioning
confidence: 84%
See 2 more Smart Citations
“…The P concentration was observed slightly higher in site 2 than the other sites. The available P concentration was very low compared with total P concentration, might be due to the abundance of Fe in the soil that may fix the excess phosphorus (Jokubauskaitė et al 2015). The total K concentration shows almost similar result in soil of all sites.…”
Section: Resultsmentioning
confidence: 86%